Effect of physical therapy treatment in infants treated for congenital muscular torticollis- a narrative review - Bashir, Amna; Fareeha Amjad; Ashfaq Ahmad; Ayesha Arooj; Syed Amir Gilani (Journal of the Pakistan Medical Association, 2022)
Congenital muscular torticollis is a problem that arises at birth or immediately after birth in which the sternocleidomastoid muscle is shortened on the afflicted side, leading to an ipsilateral rotated of the head and a contralateral rotated of the face and jaw. To determine the effectiveness of physical therapy treatment in infants treated for congenital muscular torticollis, relevant articles published between 2011 and 2020 were located using electronic databases. A total of 9 studies out of 24 potentially relevant articles were reviewed. All studies were randomised controlled trials with 6-8 score on the Physiotherapy Evidence Database scale (Pedro scale) which showed high quality of methodology. The studies typically found significant statistical effects in the management of congenital muscular torticollis. Additionally, most of the studies reported increased adherence to exercise as another essential advantage. Conservative physical therapy management showed positive outcomes, and early physiotherapy referral showed significant reduction in treatment duration. Key Words: Conservative management, Congenital muscular torticollis, Infants, Paediatric physiotherapy, Physical therapy.